Study of Various Load Balancing Techniques in Cloud Environment- A Review - Kaur, Rajdeep; Kaur, Amanpreet (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a model for delivering information technology services in which resources are retrieved from the internet through web-based tools and applications, rather than a direct connection to a server. Users can set up and boot the required resources and they have to pay only for the required resources. Thus, in the future providing a mechanism for efficient resource management and assignment will be an important objective of Cloud computing. Cloud Computing is a new trend emerging in IT environment with huge requirements of infrastructure and resources. Load Balancing is an important aspect of cloud computing environment. Efficient load balancing scheme ensures efficient resource utilization by provisioning of resources to cloud user’s on-demand basis in pay-as-you-say-manner. Load Balancing may even support prioritizing users by applying appropriate scheduling criteria.